ENHANCING STUDENT PARTICIPATION AND COMPREHENSION THROUGH YOUTUBE-BASED LEARNING MEDIA IN ISLAMIC CULTURAL HISTORY CLASSES: A CASE STUDY AT MTSN 5 JOMBANG - Usfatun Khusniyah; Hilyah Ashoumi; Lintang Ramadhani; M Wafiyul Ahdi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to examine the implementation of YouTube-based learning media in enhancing student participation and comprehension in Islamic Cultural History classes at MTsN 5 Jombang. The background of this research stems from the limited use of varied learning media, which has led to students’ low engagement and passive attitudes during lessons. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that YouTube-based learning fosters a more interactive, engaging, and enjoyable classroom atmosphere. The visual and auditory elements of YouTube videos help students grasp historical content more concretely and stimulate curiosity and learning motivation. Furthermore, teachers benefit from the platform’s accessibility, as students can revisit the videos for review and reinforcement. Nevertheless, several challenges were identified, including unstable internet connectivity and students’ tendency to focus more on video visuals rather than the instructional content. Overall, YouTube serves as an effective learning medium to improve both student participation and comprehension when appropriately integrated with teacher guidance and well-structured learning design.